Peranan Audit atas Siklus Piutang dalam Menjamin Kewajaran Penyajian Piutang pada Laporan Keuangan Perusahaan - Febri Andany; Madinatul Munawwarah; Masyhuri Masyhuri (Journal of Economic and Business Advancement, 2025)
Accounts receivable is an account that has a high level of risk of material misstatement because it is directly related to revenue recognition and estimates of future economic benefits. This study aims to analyze the role of auditing the accounts receivable cycle in ensuring the fairness of accounts receivable presentation in company financial statements. The research approach used is qualitative with a literature study method of audit textbooks, audit standards, and relevant journal articles. The discussion focuses on the role of auditing in assessing the fairness of the recognition and existence of accounts receivable, the assessment and allowance for bad debts, and the presentation and disclosure of accounts receivable in financial statements. The results of the study show that a professional and standard-compliant accounts receivable cycle audit can improve the reliability of financial statements by reducing the risk of misstatement and fraudulent practices. Auditors play an important role in evaluating internal controls, assessing management estimates, and ensuring the transparency of the information presented. This study confirms that the audit of the accounts receivable cycle is an important element in maintaining the integrity and credibility of a company's financial reporting.